SPARC Endogenous Level, rather than Fibroblast-Produced SPARC or Stroma Reorganization Induced by SPARC, Is Responsible for Melanoma Cell Growth - Prada, Federico; Benedetti, Lorena G.; Bravo, Alicia I.; Alvarez, Mariano J.; Carbone, Cecilia; Podhajcer, Osvaldo L. (Journal of investigative dermatology, 2007)
SPARC (secreted protein acidic and rich in cysteine) is a matricellular protein whose overexpression in malignant or tumor-stromal cells is often associated with increased aggressiveness and bad prognosis in a wide range of human cancer types, particularly melanoma. We established the impact that changes in the level of SPARC produced by malignant cells and neighboring stromal cells have on melanoma growth. Melanoma cell growth in monolayer was only slightly affected by changes in SPARC levels. However, melanoma growth in spheroids was strongly inhibited upon SPARC hyperexpression and conversely enhanced when SPARC expression was downregulated. Interestingly, SPARC overexpression in neighboring fibroblasts had no effect on spheroid growth irrespective of SPARC levels expressed by the melanoma cells, themselves. Downregulation of SPARC expression in melanoma cells induced their rejection in vivo through a mechanism mediated exclusively by host polymorphonuclear cells. On the other hand, SPARC hyperexpression enhanced vascular density, collagen deposition, and fibroblast recruitment in the surrounding stroma without affecting melanoma growth. In agreement with the in vitro data, overexpression of SPARC in co-injected fibroblasts did not affect melanoma growth in vivo. All the data indicate that melanoma growth is not subject to regulation by exogenous SPARC, nor by stromal organization, but only by SPARC levels produced by the malignant cells themselves.